HUBUNGAN MANAJEMEN KEPALA RUANGAN DENGAN KINERJA PERAWAT DALAM PELAKSANAAN ASUHAN KEPERAWATAN DI RUANGAN RAWAT INAP KLINIK UTAMA KAO - Dadana, Geraldin (Journal Of Community & Emergency, 2024)
Several factors influence the delivery of care, such as the role of the room manager. A study by Jakri and Timun (2019) in the inpatient department of Waerenga Public Health Center, East Manggarai District, found a significant association between the managerial function of room her managers and nurses' performance in providing nursing care. concluded. of 0.046. In another study by Maj. Gen. Ha Thalib Kerinci on the relationship between room manager's leadership style and the performance of the implementing nurse when implementing nursing in a general hospital inpatient unit, this study found a significant association between concluded. democratic and autocratic leadership styles and the performance of nurses in providing care. Also, there was no association between leadership style, participation, and laissez-faire and the performance of nurses providing care. Research Purpose It is known that there is a correlation between the management of the room manager and the performance of the nurses in the implementation of care in the hospital room of Kao Main Hospital. The type of research is analytical descriptive, the research period is November 2021, and the research location is Kao Main Institute. The statistical test used is the chi-square test with a 95% confidence level. As a result, the results of the test using the chi-square test have a p-value of 0.003, indicating a significant association between diaper use and toilet training readiness among children aged 1-3 years in the southern village of Atep Satu. has been shown to have potential. A district consisting of the Regency of Langowan and Minahasa. The conclusion of this study is that room manager leadership is superior to room manager leadership in rooms at Kao Main Hospital. The performance of nurses who nursed in the Kao hospital room was better than that of bad nurses. The proposal of this study is that this study should be a reference for further investigation of room leader's function on health workers' motivation and performance.